PRACTICAL OPTIMALISZATION ACTIVITY IN BASIC SCHOOL IN TANGKILING CENTRAL KALIMANTAN PROVINCE - Gunarjo S Budi; Risqi Agustina; Annisa Alifya Wibawa; Anggi Safitri (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2021)
This Community Service Activity (PKM) aims to motivate teachers to optimize science practicum activities in elementary schools by using tools in the laboratory or using learning media that utilize tools and materials around the school environment. This PKM activity is carried out by providing training to elementary school teachers with several methods used such as lectures, discussions, questions and answers, demonstrations and simulations. The subjects of this service activity are elementary school (SD) teachers in the Tangkiling area of Central Kalimantan province, which consist of SDN 1 Tangkiling, SDN 2 Tangkiling, and SDN 3 Tangkiling. This service is implemented in the semester 2021/2022 academic year in Palangka Raya. The data analysis technique used in this service activity is to analyze the results that have been achieved through PKM activities which are outlined in the form of activity results at each stage of activity implementation. The outputs of this service activity are: (1) increasing teacher skills in using laboratory equipment and media around the school to optimize science practicum activities at school; (2) A collection of several science practicum instructions that can be used by teachers (trainees) for one of the teaching materials that can be used in schools.